DISTRIBUTION OF SOME MICRONUTRIENTS IN THE LAKHOTIA LAKE, PALI (RAJASTHAN) - Khatri, T C (Indian Journal of Fisheries, 2011)
The distribution of four nMcronutrients â€”Fe, Zn, Cu and Mnâ€” are reported over an annual cycle in the Lakhotia lake, Rajasthan. Total Fe, Zn and Mn were present in detectable concentration throughout the year, whereas Cu only during April to August. The concentrations of total Fe ranged from 49 to 816 J-gl-’. Zn, 30 to 382 /*gl-’, Mn, 74 to 144/^gl-’ and Cu, traces to 50 P’g!-’. On a comparison with those of temperate lakes the concentrations of all micronutrients in Lakhotia lake were higher. An inverse relationship of mioronutrientsi with phytoplanktoe was apparent.